Understanding culture and HIV/AIDS in sub-Saharan Africa - Sovran, Steven (Taylor & Francis, 2013)
Early in the study of HIV/AIDS, culture was invoked to explain differences in the disease patterns between sub-Saharan Africa and Western countries. Unfortunately, in an attempt to explain the statistics, many of the presumed risk factors were impugned in the absence of evidence. Many cultural practices were stripped of their meanings, societal context and historical positioning and transformed into cofactors of disease. Other supposedly beneficial cultural traits were used to explain the absence of disease in certain populations, implicitly blaming victims in other groups. Despite years of study, assumptions about culture as a cofactor in the spread of HIV/AIDS have persisted, despite a lack of empirical evidence. In recent years, more and more ideas about cultural causality have been called into question, and often disproved by studies. Thus, in light of new evidence, a review of purported cultural causes of disease, enhanced by an understanding of the differences between individual and population risks, is both warranted and long overdue. The preponderance of evidence suggests that culture as a singular determinant in the African epidemic of HIV/AIDS falls flat when disabused of its biased and ethnocentric assumptions.